Survivalitas Guru Bahasa Arab dalam Perspektif Status dan Peran Sosial di Masyarakat - Rifqi Aulia Rahman (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
This research was triggered by the problem of the status and role of the MAN 2 Kudus Arabic teachers in the community which is not always in line with the predicate of the guru agama which is inherent when teaching in madrasa. This study aims to describe the status and role of the MAN 2 Kudus Arabic teachers in the community, explore their arguments and subjective responses from various surrounding community clusters. This research is a case study with a qualitative descriptive approach. The results of this study stated: 1) All Arabic teachers in MAN 2 Kudus had social status and roles that penetrated several social fields, including medicine, organizational leadership, and spiritual counseling; 2) the relevance of the status and role of teachers in madrasas with within the community concerns three categories, indigenous Arabic teachers and migrants. Second, Arabic teachers graduated from Arabic Education (PBA) and non-PBA graduates. Third, senior and junior Arabic teachers; 3) The views of community institutions, religious leaders, madrassas, and ordinary people, related to the social status and role, First, Arabic teachers are not identical with guru agama. Second, Arabic teachers are identical to guru agama.